Brown Fat Expresses Adiponectin in Humans - Gianluca Iacobellis; Cira Di Gioia; Luigi Petramala; Caterina Chiappetta; Valentina Serra; Laura Zinnamosca; Cristiano Marinelli; Antonio Ciardi; Giorgio De Toma; Claudio Letizia (International Journal of Endocrinology)
The presence of brown adipose tissue (BAT) in humans is unclear. Pheochromocytomas (PHEO) are rare tumors of neuroectodermal origin which occur in 0.1-0.2% of patients with hypertension. We sought to evaluate the presence and activity of BAT surrounding adrenal PHEO in a well-studied sample of 11 patients who were diagnosed with PHEO and then underwent adrenalectomy. Areas of white fat (WAT) and BAT surrounding PHEO were obtained by Laser Capture Microdissection for analysis of uncoupling protein (UCP)-1 and adiponectin mRNA expression. Adiponectin and UCP-1 mRNA levels were significantly higher in BAT than in WAT (0.62 versus 0.15 and 362.4 versus 22.1, resp., for both). Adiponectin mRNA levels significantly correlated with urinary metanephrines (, ), vanilly mandelic acid (VMA) (, ), and serum adiponectin levels (, ). Serum adiponectin levels significantly decreased ( μg/mL versus  μg/mL, ) after adrenalectomy in PHEO subjects. This study provides the following findings: (1) BAT surrounding PHEO expresses adiponectin and UCP-1 mRNA, (2) expression of adiponectin mRNA is significantly higher in BAT than in WAT surrounding PHEO, and (3) catecholamines and serum adiponectin levels significantly correlate with BAT UCP-1 and adiponectin mRNA.